Current status and prospects for efficient aquaculture of the African bonytongue, Heterotis niloticus (Cuvier, 1829): Review - Missinhoun Dagoudo; David Benhaïm; Elie Montchowui (Journal of the World Aquaculture Society)
Abstract The aquaculture industry plays a crucial role in global food production and is expected to expand in response to the increasing demand for aquatic products. To sustain this growth, aquaculturists must develop new strategies and improve existing practices to address various challenges. In Africa, the sustainable development of aquaculture could be achieved not only by intensifying and integrating breeding techniques for species like Tilapia and Catfish but also by developing and domesticating other promising species with high aquaculture potential. Identifying and understanding these species is vital for overcoming these challenges. Heterotis niloticus is one such valuable species for aquaculture in Africa, offering several advantages including its air‐breathing capability, high market value, excellent meat quality, omnivorous diet, resilience to stress, ability to survive in low‐oxygen water, and consumer acceptance. In captivity, it has shown significant growth, with individual mean body mass reaching 3 to 5 kg in 12 months. These findings highlight the potential of Heterotis niloticus to enhance aquaculture production, not only in Africa but also globally. However, challenges remain, such as high mortality during early life stages, the determination of its nutritional needs at various ontogenetic stages, and the development of efficient breeding practices. Further research is required in areas like nutrition, physiology, breeding technology, genetics, economics, and environmental impact to optimize the culture of this species.